Hydrate seeding effect on the metastability of CH4 hydrate - Baek, Seungjun; Lee, Wonhyeong; Min, Juwon; Ahn, Yun-Ho; Kang, Dong Woo; Lee, Jae W. (The Korean journal of chemical engineering, 2020)
Cyclopentane (CP) hydrate seeds can lead to nucleation of CH 4 hydrate with a lower supersaturation; the concept of nucleation potential was applied to estimate the metastable zone width (MSZW) of CH 4 hydrate. To verify the crystal structure of CH 4 hydrate formed from the CP hydrate seeds, the hydrate samples were analyzed by high resolution powder diffraction (HRPD). 1 wt% of CP hydrates in the system reduced the MSZW of CH 4 hydrate from 3.39 K to 1.32 K, and showed synergetic performance with sodium dodecyl sulfate (SDS). From the hydrate nucleation theory, SDS is able to decrease the effective surface energy for heterogeneous nucleation on the stainless steel wall, but the CP hydrate seeds provide new nucleation sites with even lower surface energy than that of the stainless steel wall. Hence, the nucleation rate depends on the amount of CP hydrate seeds, and the kinetic parameter can be estimated from the concentration of nucleation sites on the CP hydrate seeds. Also, the MSZW of CH 4 hydrate was satisfactorily correlated with the amount of CP hydrate seeds by the cumulative nucleation potentials using estimated kinetic parameters.